Nitric Oxide Pathways in Neurovascular Coupling Under Normal and Stress Conditions in the Brain: Strategies to Rescue Aberrant Coupling and Improve Cerebral Blood Flow - Lourenço, Cátia F.; Laranjinha, João (Frontiers in Physiology, 2021)
The brain has impressive energy requirements and paradoxically very limited energy reserves implying a huge dependency on a continuous blood supply. Additionally, it must be dynamically regulated to the areas of increased neuronal activity and, thus, of increased metabolic demands. The coupling between neuronal activity and CBF is supported by a mechanism called neurovascular coupling (NVC). Amongst several vasoactive molecules released by glutamatergic activation, nitric oxide (•NO) is recognized to be a key player in the process and essential for the development of the neurovascular response. Classically, •NO is produced in neurons upon activation of glutamatergic NMDA receptor by the neuronal isoform of nitric oxide synthase and promotes vasodilation by activating soluble guanylate cyclase in the smooth muscle cells of the adjacent arterioles. This pathway is part of a more complex network in which other molecular and cellular intervenients, as well as other sources of •NO, are involved. The elucidation of these interacting mechanisms is fundamental to understand how the brain manages its energy requirements and how the failure of this process translates into neuronal dysfunction. Here we aim to provide an integrated and updated perspective of the role of •NO in the NVC, incorporating the most recent evidence that reinforce its central role in the process from both viewpoints, as a physiological mediator and a pathological stressor. First, we describe the glutamate-NMDA receptor-nNOS axis as a central pathway in NVC, then we review the link between the derailment of NVC and neuronal dysfunction associated with neurodegeneration (with a focus on Alzheimer’s disease). We further discuss the role of oxidative stress in the NVC dysfunction, specifically by decreasing •NO bioavailability and diverting its bioactivity towards cytotoxicity. Finally, we highlight some strategies targeting the rescue or maintenance of •NO bioavailability that could be explored to mitigate the NVC dysfunction associated with neurodegenerative conditions. In this line, the potential modulatory effects of dietary nitrate and polyphenols on •NO-dependent NVC, in association with physical exercise, may be used as effective non-pharmacological strategies to promote the •NO bioavailability and thereby to manage NVC dysfunction in neuropathological conditions.